2006
DOI: 10.1271/bbb.70.1110
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Cl-Activated Aminopeptidase from Bovine Skeletal Muscle

Abstract: To elucidate the mechanisms involved in the increase in free amino acids during postmortem storage of meat, a novel aminopeptidase was purified from bovine skeletal muscle by ammonium sulfate fractionation and successive chromatographies such as DEAE-cellulose, Sephacryl S-200, Hydroxyapatite, Phenyl-Sepharose, and Hi-Trap affinity column chromatography. The molecular mass of the enzyme was found to be 58 kDa on SDS-PAGE. This enzyme had optimum pH at around 7.5, and preferably hydrolyzed Ala-beta-naphthylamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Therefore the current results suggest that Phaffia yeast can influence meat aging during storage to improve the taste of meat. Even today there are no studies about effect of dietary carotenoids on free amino acid content alteration of broiler meat during postmortem storage, but the increase in free amino acids during the postmortem storage of meat is caused by the action of amino‐peptidases and proteases (Migita & Nishimura ). The enzymatic reactions in the proteolytic system are affected by meat pH reduction (Moya et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the current results suggest that Phaffia yeast can influence meat aging during storage to improve the taste of meat. Even today there are no studies about effect of dietary carotenoids on free amino acid content alteration of broiler meat during postmortem storage, but the increase in free amino acids during the postmortem storage of meat is caused by the action of amino‐peptidases and proteases (Migita & Nishimura ). The enzymatic reactions in the proteolytic system are affected by meat pH reduction (Moya et al .…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition is thought to be by reduction of the disulphide bonds. Many aminopeptidases have been reported to be unaffected by β-mercaptoethanol and some even show enhanced activity in the presence of reducing agents like DTT [32]. However, leucine aminopeptidases from Bacillus sp.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…The final protein degradation products, such as peptides and free amino acids were thought to be (1971) found that large increases in alanine, glutamine, serine, valine, leucine and lysine are obtained by ageing of beef for 5 d. Nishimura (1998) reported that rates increase in free amino acids of beef during the postmortem was 3 µmol/g meat per day, especially while large increases were in alanine, leucine, serine and valine. In addition, Migita and Nishimura (2006) suggested that amino peptidase D which newly-found distinct from amino peptidase B appears to contribute the increase in free amino acids, especially alanine and glutamine in meat during ageing. In this study, only sulphur-amino acid like cystine was not significantly differed between ageing days.…”
Section: Resultsmentioning
confidence: 99%